A multi-agent systems approach to microeconomic foundations of macro - Bill Gibson (University of Massachusetts, Department of Economics, 2007)
This paper is part of a broader project that attempts to generate microfoundations for macroeconomics as an emergent property of complex systems. The multi-agents systems approach is seen to produce realistic macro properties from a primitive set of agents that search for satisfactory activities, jobs, in an informationally constrained, computationally noisy environment. There is frictional and structural unemployment, in.ation, excess capacity, financial instability along with the possibility of relatively smooth expansion. There is no Phillips curve but an inegalitarian distribution of income emerges as fundamental property of the system.
Keywords: 330